Growth Dynamics of selected Vibrio spp. in mono-, co-culture and multi-bacterial microcosms: Investigating the prevalence of Vibrio parahaemolyticus in seawater - Shirri Ganaesh Murugan; Choon Weng Lee; Walter Aaron Chun Ying Wong; Yi You Wong; Boyu Liu; Kumaran Narayanan; Edmund Ui Hang Sim; Chui Wei Bong; Aijun Wang (Marine Environmental Research, 2026)

Commercial food environment and cognitive health: findings from 114 urban communities - Weiju Zhou; Deanna Sim; Yanxi Zeng; He Li; Xiangwei Dai; Yaojing Chen; Jiuxuan Gao; Yue Ma; Ying Long; Zhanjun Zhang; John S. Ji (Environmental Research, 2026)

Texture engineering in cell-based seafood: Insights from structural and compositional benchmarks - Shaon Xin Ying Chuah; Karen M. Mancera Azamar; Tanmayee Kolli; Asli Z. Odabasi; Boce Zhang; Charles Sims; Renee Goodrich-Schneider; Ana M. Porras; Razieh Farzad (Food Research International, 2025)

Persistent Genomic Erosion in Whooping Cranes Despite Demographic Recovery - Claudia Fontsere; Samuel A. Speak; Andrew J. Caven; Juan Antonio Rodríguez; Xuejing Wang; Carolina Pacheco; Molly Cassatt‐Johnstone; Georgette Femerling; Brigid Maloney; Jennifer Balacco; Joanna Collins; Ying Sims; et al. (Molecular Ecology, 2025)
Integrating in‐situ (wild) and ex‐situ (captive) conservation efforts can mitigate genetic diversity loss and help prevent extinction of endangered wild populations. The whooping crane ( Grus americana ) experienced severe population declines in the 18th century, culminating in a collapse to ~20 individuals by 1944. Legal protections and conservation actions have since increased the census population from a stock of 16 individuals to approximately 840 individuals, yet the impact on genomic diversity remains unclear. We analysed the temporal dynamics of genomic erosion by sequencing a high‐quality reference genome, and re‐sequencing 16 historical (years 1867–1893) and 37 modern (2007–2020) genomes, including wild individuals and four generations of captive‐bred individuals. Genomic demographic reconstructions reveal a steady decline, accelerating over the past 300 years with the European settlement of North America. Temporal genomic analyses show that despite demographic recovery, the species has lost 70% of its historical genetic diversity and has increased its inbreeding. Although the modern population bottleneck reduced the ancestral genetic load, modern populations possess more realised load than masked load, possibly resulting in a chronic loss of fitness. Integrating pedigree and genomic data, we underscore the role of breeding management in reducing recent inbreeding. Yet ongoing heterozygosity loss, load accumulation, and persistent effects of historical inbreeding (i.e., background inbreeding) argue against the species' downlisting from its current Endangered status on the IUCN Red List and the Endangered Species Act. The presence of private genetic variation in wild and captive populations suggests that wild‐captive crosses could enhance genetic diversity and reduce the realised load. Our findings emphasise the role of genomics in informing conservation management and policy.

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.

From electronic wastes to efficient and specific filtration membranes: A photovoltaic upcycling case enabling silver urban mining - Bo Han; Ying Sim; Qingyu Yan; Nripan Mathews; Jean-Christophe P. Gabriel (Journal of Cleaner Production, 2025)

Fatty acid esters of 3-monochloropropane-1,2-diol and glycidol in palm oil: A review on current industrial-scale mitigation strategies, challenges and perspectives - Yi Hui Ong; Cher Pin Song; Wee Sim Choo; Yee Ying Lee; Kiat Seng Qua; Wei Ping Quek; Eng-Seng Chan (Food Research International, 2025)

The Impact of Anthropogenic Pollution on Tidal Water Quality in Mangrove Wetlands - Kit-Ling Lam; Yu-Hin Lam; Angie Ying-Sim Ng; Ken Kwok-Yin So; Nora Fung-Yee Tam; Fred Wang-Fat Lee; Wing-Yin Mo (Journal of Marine Science and Engineering, 2023)
Mangrove wetlands are vulnerable coastal ecosystems that provide critical habitats for aquatic life. Tai O is a popular tourist village on Lantau Island, Hong Kong, which is surrounded by mangrove wetlands with rich biodiversity; and this village is also famous for its traditional stilt houses. However, the untreated municipal sewage from some stilt houses is directly discharged into nearby tidal channels, potentially threatening health of the adjacent mangrove wetlands. In order to evaluate the anthropogenic impact on these wetlands and identify the potential sources of their pollution, this study aimed to evaluate spatial (at the sampling points) and temporal (during weekdays and weekends) differences in the quality of their tidal water, and examine relationships between the water quality and the density of the stilt houses. The results indicated that the water quality was worse during weekends. The ammonia concentrations in most samples exceeded the limits of the Hong Kong Water Quality Objectives, China’s Sea Water Quality Standards, and even the U.S. EPA criterion for fish reproduction. This high ammonia input could potentially adversely affect the mangrove ecosystem, underscoring the need for further comprehensive studies. Moreover, some of the weekend water samples had lower dissolved oxygen levels and were polluted by phosphate. Our Principal Component Analysis revealed that water quality was correlated with stilt house density, suggesting that anthropogenic inputs of untreated sewage was the major source of pollution. These findings highlight that nutrients released from human activities, particularly ammonia and phosphate, must be controlled for a better protection of mangrove wetland ecosystems.

Sea urchins of Peninsular Malaysia: Spatial distribution and species-habitat association - Man Ying Mok; Yang Amri Affendi; Jillian Lean Sim Ooi (Regional Studies in Marine Science, 2023)

A facile crush-and-sieve treatment for recycling end-of-life photovoltaics - Ying Sim; Yeow Boon Tay; Huu Khue Pham; Nripan Mathews (Waste Management, 2023)

Habitat Adaptation Mediates the Influence of Leaf Traits on Canopy Productivity: Evidence from a Tropical Freshwater Swamp Forest - Weng Ngai Lam; Pin Jia Chan; Ying Ying Ting; Hong Jhun Sim; Jun Jie Lian; Rie Chong; Nur Estya Rahman; Lorraine Wen Ai Tan; Qian Yi Ho; Zhongyu Chiam; Srishti Arora; Hao Ran Lai; et al. (Ecosystems, 2022)

First report of Nigrospora aurantiaca causing leaf spot on Pandanus amaryllifolius in Malaysia - Ying Wei Khoo; Hui Teng Tan; Yam Sim Khaw; Shi-Fang Li; Khim Phin Chong (Journal of Plant Pathology, 2022)

Chromosome-level Genome Assembly of Acanthopagrus latus Provides Insights into Salinity Stress Adaptation of Sparidae - Jianguo Lu; Dong Gao; Ying Sims; Wenyu Fang; Joanna Collins; James Torrance; Genmei Lin; Jingui Xie; Jian Liu; Kerstin Howe (Marine Biotechnology, 2022)

Feasibility and utility of facemask sampling in the detection of SARS-CoV-2 during an ongoing pandemic - Dorothy Hui Lin Ng; Mei Yi Sim; Hong Hong Huang; Jean Xiang Ying Sim; Jenny Guek Hong Low; Jay Kheng Sit Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Spatial and Structural Factors Shape Seagrass-Associated Bacterial Communities in Singapore and Peninsular Malaysia - Golam Rabbani; Bertrand Chengxiang Yan; Nicole Li Ying Lee; Jillian Lean Sim Ooi; Jen Nie Lee; Danwei Huang; Benjamin J. Wainwright (Frontiers in Marine Science, 2021)
Plant-microbe relationships play critical roles in the functioning and health of terrestrial plants, but little is known about this relationship in marine angiosperms such as seagrasses. Here, we investigated the microbial communities associated with the seagrass Enhalus acoroides throughout Singapore and Peninsular Malaysia. At each sampling location we collected 10 individual and unconnected plants. Each plant was subsequently broken down into leaves, roots, and rhizomes. In addition to living plant parts a sediment sample was taken in close proximity to each. Using high throughput 16S rRNA gene amplicon sequencing we characterised the bacterial communities associated with each plant part and the associated sediment sample. Results indicate geographic structuring of bacterial communities, with a significant pattern of distance decay suggesting dispersal limitation is a contributing factor to the differences we see in bacterial community structure. Bacterial communities can be further differentiated by the function of the collected sample (leaf, root, and rhizome), and we identified a number of microbial indicator species that are associated with each plant part. Further analysis revealed the presence of several microbial taxa that have previously been identified as indicators of “unhealthy” or “stressed” seagrass meadows. This study addresses a current scientific gap related to the characterisation of seagrass microbiomes, and provides a foundation on which future studies can build, particularly those in the Southeast Asian seagrass biodiversity hotspot.

Utilization of Descriptive Sensory Analysis and Volatile Analysis to Determine Quality Indicators of Aquacultured Whiteleg Shrimp ( Litopanaeus vannemei ) during Refrigerated Storage - Ying Fan; Asli Odabasi; Charles Sims; Keith Schneider; Zhifeng Gao; Paul Sarnoski (Journal of Aquatic Food Product Technology, 2020)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Trade-offs between defence and competition in gregarious juvenile fluted giant clams (Tridacna squamosa L.) - Darren Z. H. Sim; Mei Lin Neo; Ambert C. F. Ang; Lynette S. M. Ying; Peter A. Todd (Marine Biology, 2018)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)